Pengaruh Penyuluhan pada Penjual Gorengan tentang Keamanan Pangan terhadap Kandungan Logam Berat (Pb dan Zn) Gorengan di Sepanjang Jalan Kaliurang Yogyakarta - Elza Ismail; Tjarono Sari (Poltekkes Kemenkes Yogyakarta, 2016)
Background: Food is a basic need for human growth, maintenance, health improvement. The goodfood mean is free from biology and chemistry impurities, and other substances that are harmful for human health such as heavy metal contamination of lead (Pb) and zinc (Zn). Lead found at vehicle exhaust fumes and water can be a poison that damages the central nervous system. Although zinc is needed for the body, zinc can be toxic if it is over consumed. Zinc can be found in cooking utensils, water, and air. Foods sold on the roadside have great risksof impurities exposition of Pb and Zn, one of them is fried foods that are highly preferred by people. Objective: To find out the food safety of fried foods that are sold along Kaliurang street, Sleman, Yogyakarta based on chemical impurities of Pb and Zn Method: This research was a descriptive observational with cross sectional study design. The data obtained were analyzed descriptively. The sample consists of 9 fried foods (it was known as tahu isi, fried tofu filled with vegetables) which were cooked on the street and exposed to 2 hours. The samples were raw tofu and fried tofu. This research was conducted at Health Laboratory Hall Yogyakarta quantitatively with AAS method. Results: 100% of samples containing lead level between 0.1 to 0.6 mg/kg and zinc levels 12 to 15 mg/kg. The lead level of 77,7% of the sample ≥ the maximum level to consume, with 22.2% sample ≤ the maximum level to consume, that is 0.25 mg/kg. The lead level was increased from raw to fried tofu to after-2-hour-exposed tofu. The level of zinc in 100% of samples ≤ tolerable upper intake level (40 mg/kg).The difference of the zinc level in raw, fried, after a 2-hour exposed tofuwas caused by the use of water, the frying pan, and the condition of the contaminated air. Conclusion: The food safety of fried foods based on the lead impurities was 22.2% of the samples was safe to consume and 77,2% of the sample was not safe to consume, while based on the impurities of zinc, 100% of the sample was safe to consume. Keywords: Fried food, food safety, lead (Pb) level, zinc (Zn) level.